2010
DOI: 10.1523/jneurosci.0157-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Aβ-Mediated NMDA Receptor Endocytosis in Alzheimer's Disease Involves Ubiquitination of the Tyrosine Phosphatase STEP61

Abstract: Amyloid ␤ (A␤) is involved in the etiology of Alzheimer's disease (AD) and may contribute to cognitive deficits by increasing internalization of ionotropic glutamate receptors. Striatal-enriched protein tyrosine phosphatase 61 (STEP 61 ), which is targeted in part to the postsynaptic terminal, has been implicated in this process. Here we show that STEP 61 levels are progressively increased in the cortex of Tg2576 mice over the first year, as well as in prefrontal cortex of human AD brains. The increased STEP 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
265
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(291 citation statements)
references
References 52 publications
21
265
0
1
Order By: Relevance
“…STEP mediates AMPA and NMDA receptor subunit endocytosis through tyrosine dephosphorylation of their subunits (Zhang et al, 2008;Zhang et al, 2010Zhang et al, , 2011Kurup et al, 2010). In agreement with a recent study (Sun et al, 2013), we found that cocaine reduced the phosphorylation level of the NMDAR subunit GluN2B, an effect prevented by ZM241385 and absent in stA 2A RKO.…”
Section: Discussionsupporting
confidence: 92%
“…STEP mediates AMPA and NMDA receptor subunit endocytosis through tyrosine dephosphorylation of their subunits (Zhang et al, 2008;Zhang et al, 2010Zhang et al, , 2011Kurup et al, 2010). In agreement with a recent study (Sun et al, 2013), we found that cocaine reduced the phosphorylation level of the NMDAR subunit GluN2B, an effect prevented by ZM241385 and absent in stA 2A RKO.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, eNMDAR-mediated increases in NO generation, tau protein, tau hyperphosphorylation, and caspase-3 activity that we found in response to oligomerized Aβ argue that these early molecular events presage the loss of synapses that we observed hours later. Prior experiments had shown that after acute exposure to Aβ (10,32,63), other synaptic events also may occur, such as internalization via endocytosis of postsynaptic receptors to account for a decrease in mEPSC amplitude. However, this mechanism alone would not adequately account for the decrease in mEPSC frequency (but not amplitude) that we observed after chronic Aβ exposure in the hAPP-J20 hippocampus and that was reversed, at least partially, with prolonged memantine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…S4). In line with this scenario, the Aβ-dependent endocytosis of NMDARs requires phosphatase activity, and tyrosine dephosphorylation of GluN2B correlates with GluN1/GluN2B endocytosis (46,47). Interestingly, EphB2, a receptor tyrosine kinase that selectively controls the synaptic localization and function of GluN2B-containing NMDARs in mature neurons (48), has been implicated in the synapto-toxic effects of Aβ oligomers (8,49,50).…”
Section: Discussionmentioning
confidence: 87%